TINJAUAN HUKUM ISLAM TERHADAP PRAKTEK PISUKE DALAM PERKAWINAN DI DESA DARMAJI KECAMATAN KOPANG - Lalu Yoga Vandita (LPPM Institut Pendidikan Nusantara Global, 2022)
In Indonesia, which has many tribes and cultures, it turns out that there are many ways to carry out the institution of marriage in every region. In Lombok, for example, marriage is so sacred and full of traditional content, that to hold a wedding, you have to try hard to go through a series of customs, one of which is pisuke, where the male family must pay an amount of money that has been determined by the female family as a sign to be able to hold it. wedding. To facilitate understanding in this writing, we use research methods including; by digging up and digging up data sources from various literature relating to pisuke practice. The contract is clear, the goods being contracted are halal and holy, therefore pisuke in the view of Islamic law is permissible because there has been an agreement between the two parties.